New momentum for data, government investment in technology, and high-quality urban development in the yellow river basin - Jin, Hao; Yang, Nan (Frontiers in Environmental Science, 2022)
The “Great Protection, Great Governance” strategy requires efficient environmental protection in the Yellow River Basin (YRB), enhancement of transformation between the old and new momentums, and high-quality development (HQD) of the region. This research explores the impact of the new momentum for data and government investment in technology on the HQD level of 62 cities in the YRB. The data used in this paper are collected from 2008 to 2020. We construct the index system and apply the analytic hierarchy process and entropy value method to calculate the HQD level of 62 cities in the YRB. We also construct the spatial Durbin model to investigate the influence mechanism of the above factors on the HQD of cities in the YRB and their effects from the perspectives of the new momentum for data and government investment in science and technology. According to the research results, the level of high-quality urban development of the YRB exhibits a stable increase in time series and an overall spatial distribution pattern of “higher in the east-west and lower in the middle” and “higher in the south and lower in the north”. The new momentum for data and government investment in technology significantly contribute to the HQD of cities in the YRB, with significant spatial spillover effects. The new momentum for data and government investment in technology have a positive impact on the HQD of a city and the neighboring cities. Meanwhile, the level of human capital, government intervention, scientific and technological (S&T) innovation, and openness contribute significantly to high-quality urban development. The government and policymakers should focus on the prominent role of new momentum for data and government investment in technology and design long-term feasible strategies to improve the high-quality urban development in a new stage.